2016
DOI: 10.1177/0011000016666156
|View full text |Cite
|
Sign up to set email alerts
|

Veterans’ Perspectives on the Psychosocial Impact of Killing in War

Abstract: Based on focus group and individual interviews with 26 combat veterans, this qualitative thematic analysis examines the psychosocial and interpersonal consequences of killing in war. It describes the consequences that veterans identify as most relevant in their lives, including postwar changes in emotions, cognitions, relationships, and identity. Furthermore, it illustrates the linked psychological and social dimensions of those consequences—namely, how the impact of killing in war is rooted in the unique pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(93 citation statements)
references
References 46 publications
4
86
0
Order By: Relevance
“…In addition, whereas Criterion A events are often characterized by a threat to life or physical integrity, MI events fundamentally entail a perceived violation of moral beliefs/values that lead an individual to appraise his or her experience as “wrong.” In addition to military sexual trauma, MI events could therefore include other types of betrayals by peers, leadership, trusted civilians as well as acts of harm inflicted on others (e.g., revenge or retribution and destruction of civilian property), incidents involving death or harm to civilians, harm committed within military ranks, inability to prevent the death/suffering of comrades or civilians, and ethical dilemmas (Currier, Holland, Drescher, & Foy, ). Multiple studies have also consistently linked PMIEs with forms of psychological sequelae that are often not linked as strongly with physical threat stressors (e.g., Jordan, Eisen, Bolton, Nash, & Litz, ; Purcell, Koenig, Bosch, & Maguen, ; Stein et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, whereas Criterion A events are often characterized by a threat to life or physical integrity, MI events fundamentally entail a perceived violation of moral beliefs/values that lead an individual to appraise his or her experience as “wrong.” In addition to military sexual trauma, MI events could therefore include other types of betrayals by peers, leadership, trusted civilians as well as acts of harm inflicted on others (e.g., revenge or retribution and destruction of civilian property), incidents involving death or harm to civilians, harm committed within military ranks, inability to prevent the death/suffering of comrades or civilians, and ethical dilemmas (Currier, Holland, Drescher, & Foy, ). Multiple studies have also consistently linked PMIEs with forms of psychological sequelae that are often not linked as strongly with physical threat stressors (e.g., Jordan, Eisen, Bolton, Nash, & Litz, ; Purcell, Koenig, Bosch, & Maguen, ; Stein et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PTSD's Criterion D requires that negative trauma‐related beliefs, expectations, and cognitions are “exaggerated” (D2) or “distorted” (D3) attempts to make sense of the reality and consequences of trauma (American Psychiatric Association, ). In contrast, beliefs related to MI stem from evaluative cognitions and moral judgments regarding right and wrong (Purcell et al, ). For example, although PTSD is often characterized by strong negative beliefs that can be objectively compared against existing data and experience (e.g., “The world is not a safe place”), clinical evidence instead suggests that morally injured veterans typically manifest prescriptive beliefs that express core moral values (e.g., “The world should be a safe place”; Farnsworth et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative studies of moral injury with both combat Veterans (Vargas, Hanson, Kraus, & Foy, 2013;Purcell, Koenig, Bosch, & Maguen, 2016) and mental health clinicians (Drescher et al, 2011) found that in addition to the psychological problems commonly associated with PTSD, spiritual and social functioning is often negatively impacted after war. Combat Veterans from multiple eras, many of whom completed existing EBPs for PTSD, such as PE and CPT, reported continued moral, interpersonal, spiritual, and existential concerns related to killing in war (Purcell et al, 2016).…”
mentioning
confidence: 99%
“…After 14 interviews, we reached saturation in our coding process, and no longer needed to recruit additional Veterans for the study. To ensure “authenticity and fairness” in our analytic process and our presentation of data, quotes from each participant are reflected at various points in the results (Morrow, ; Purcell et al, ). These methods of coding have been used in other moral injury qualitative studies (Purcell et al, ).…”
Section: Methodsmentioning
confidence: 99%